Metody fizykochemiczne w inżynierii materiałowej. Tom 1: Właściwości fizykochemiczne magnetycznych nanocząstek tlenku żelaza wytworzonych metodą współstrącania - Marć, Maciej; Wolak, Wiktor W.; Drzewiński, Andrzej; Dudek, Mirosław R. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The monograph aims to describe in an accessible way the basic methods used in analyzing the physicochemical properties of iron oxide nanoparticles and composite materials in which such nanoparticles have been placed. The procedure for synthesizing Fe3O4 magnetic nanoparticles by co-precipitating iron (II) and (III) ions in an alkaline environment is presented in detail. It also shows how to synthesize such nanoparticles in porous and mesoporous materials. The results of studies using various types of mesoporous silicas and titanate nanotubes are presented.
Keywords: nanocząstki magnetyczne; dyfrakcja rentgenowska; spektroskopia ramanowska; rezonans ferromagnetyczny; potencjał zeta; magnetic nanoparticles; X-ray diffraction; Raman spectroscopy; ferromagnetic resonance; zeta potential